Evaluación de la gestión administrativa del GAD Parroquial Quiroga cantón Bolívar para la mejora de los servicios que brinda periodo 2020-2021 - Cedeño Vera, María Estefanía (2022)
The investigation was developed at the GAD in Quiroga parish with the objective of evaluating the administrative management, for the improvement of the services that offers to the citizenship and therefore guarantee the quality in the provision of it. Regarding the methodology applied, three phases were developed: in the first, a review of the administrative processes was carried out in order to identify the services, using a technical visit that contributed to specify the first approaches with the representative of the institution, in addition, an interview was applied for the respective characterization. In the second stage, the services were evaluated, applying a survey to 249 users, who were selected through a simple random sampling, they expressed their criteria by answering 19 questions distributed in five dimensions: tangibility, reliability, responsiveness, security, and empathy. In the third phase, an action plan was suggested where activities are proposed to reduce the shortcomings found. Regarding the results, deficiencies associated with the guide materials, work environment, the interest shown by the server to the user, the attention time and the equality in the treatment are evident, concluding through the diagnosis that there is a need to permanently measure the human and material resources used in the service provision process, due to the fact that the measured indicators have not been developed, nor have they reached the minimum required level, corresponding to 90%.